Epicardial and Paracardial Adipose Tissue Volume and Attenuation – Association with High-Risk Coronary Plaque on Computed Tomographic Angiography in the ROMICAT II Trial - Lu, Michael T. (Atherosclerosis, 2016)
BACKGROUND AND AIMS: To determine whether epicardial (EAT) and paracardial adipose tissue (PAT) volume and attenuation are associated with high-risk coronary plaque features. METHODS: In subjects with suspected acute coronary syndrome (ACS) enrolled in the ROMICAT II trial, EAT and PAT volumes indexed to body surface area (BSA) and attenuation were measured on noncontrast coronary artery calcium score (CACS) CT. High-risk plaque features (napkin-ring sign, positive remodeling, low density plaque, spotty calcium) and stenosis were assessed on coronary CT angiography (CTA). The association of EAT and PAT volume and attenuation with high-risk plaque and whether this was independent of clinical risk assessment, CACS and significant coronary artery disease (CAD) was determined. RESULTS: Of 467 (mean 54±8 yrs, 53% male) with CACS and CTA, 167 (36%) had high-risk plaque features. Those with high-risk plaque had significantly higher indexed EAT (median 59 (Q1–Q3:45–75) cc/m(2) vs. 49 (35–65) cc/m(2), p <0.001) and PAT volume (median:51 (36–73) cc/m(2) vs. 33 (22–52) cc/m(2), p <0.001). Higher indexed EAT volume was associated with high-risk plaque [univariate OR 1.02 (95%-CI:1.01 – 1.03) per cc/m(2) of EAT, p <0.001], which remained significant [univariate OR 1.04 (95%-CI:1.00–1.08) per cc/m(2) of EAT, p=0.040] after adjustment for risk factors, CACS, and stenosis ≥50%. Higher indexed PAT volume was associated with high-risk plaque in univariate analysis [OR 1.02 (1.01 – 1.03) per cc/m(2) of PAT, p <0.001], though this was not significant in multivariate analysis. At a threshold of >62.3 cc/m(2)(,) EAT volume was associated with high-risk plaque [univariate OR 2.50 (95%-CI:1.69–3.72), p <0.001)], which remained significant [OR 1.83 (95%-CI:1.10–3.05), p=0.020] after adjustment. Subjects with high-risk plaque had lower mean attenuation EAT (−88.1 vs. −86.9 HU, p=0.008) and PAT (−106 vs. −103 HU, p <0.001), though this was not significant in multivariable analysis. CONCLUSIONS: Greater volumes of EAT are associated with high-risk plaque independent of risk factors, CACS and obstructive CAD. This observation supports possible local influence of EAT on development of high-risk coronary plaque.